Recent developments in trade and competition issues in the services sector : a review of practices in travel and tourism (UN New YorkUS, 1999)
Maps out the market structure and private anticompetitive activities that have been thrown up by recent developments in the air transport and travel and tourism markets.
Keywords: COMPETITION